2006
DOI: 10.1128/iai.00257-06
|View full text |Cite
|
Sign up to set email alerts
|

Identification, Recombinant Expression, Immunolocalization in Macrophages, and T-Cell Responsiveness of the Major Extracellular Proteins of Francisella tularensis

Abstract: A safer and more effective vaccine than the previously developed live attenuated vaccine is needed for combating Francisella tularensis, a highly infectious bacterial pathogen. To search for potential candidates for inclusion in a new vaccine, we characterized the proteins present in the culture filtrates of a virulent recent clinical isolate and the attenuated live vaccine strain of F. tularensis using a proteomic approach. We identified a total of 12 proteins; among these, catalase-peroxidase was much more a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
69
1
3

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 60 publications
(76 citation statements)
references
References 42 publications
3
69
1
3
Order By: Relevance
“…However, an oxidative stress regulator OxyR is present in F. tularensis that regulates the expression of KatG and AhpC. 4 F. tularensis KatG, SodC, and AhpC are induced in response to oxidative stress (52) and are secreted in abundance in the extracellular milieu and into the cytosol of F. tularensis-infected macrophages (27). Expression of these primary antioxidant enzyme genes starts immediately upon phagocytosis of F. tularensis and remains significantly up-regulated during phagosomal and cytosolic phases (52), suggesting that F. tularensis experiences oxidative stress at both of these intracellular locations.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, an oxidative stress regulator OxyR is present in F. tularensis that regulates the expression of KatG and AhpC. 4 F. tularensis KatG, SodC, and AhpC are induced in response to oxidative stress (52) and are secreted in abundance in the extracellular milieu and into the cytosol of F. tularensis-infected macrophages (27). Expression of these primary antioxidant enzyme genes starts immediately upon phagocytosis of F. tularensis and remains significantly up-regulated during phagosomal and cytosolic phases (52), suggesting that F. tularensis experiences oxidative stress at both of these intracellular locations.…”
Section: Discussionmentioning
confidence: 99%
“…The antioxidant enzymes of F. tularensis are strategically localized to protect it from macrophage-derived oxidative insult. The iron-containing superoxide dismutase (SodB) is constitutively expressed and secreted (26,27); and the copper-zinc-containing SodC is located in the periplasmic space. Previous studies from our laboratory with mutants of F. tularensis LVS in genes encoding for the antioxidant enzymes sodB, sodC, sodBC, and those of Lindgren et al (28)., with catalase (katG), have shown that these antioxidant enzymes are required for intramacrophage survival and virulence in mice (26,29,30).…”
mentioning
confidence: 99%
“…Signals were developed by reacting with chemiluminescence substrate (Pierce) and detected by exposure to X-ray film. The nitrocellulose membrane was treated with Restore Plus Western Blot Stripping Buffer (Pierce) and reprobed with rabbit polyclonal antibodies specific for F. tularensis catalase/peroxidase (KatG) or bacterioferritin (Bfr) (18) and subsequently with goat anti-rabbit IgG (Bio-Rad, Hercules, CA), and signals were developed by reacting with chemiluminescence substrate as described above.…”
Section: Methodsmentioning
confidence: 99%
“…The susceptibility of mice to FT LVS and the ability to elicit protective immunity following a sublethal infection with this organism have allowed researchers in the field an experimental model to tease apart the interaction between FT and the host adaptive immune responses outside of BSL-3 conditions. Recent studies have begun to shed light on the extracellular proteins and potential secretion mechanisms of various strains of F. tularensis (133)(134)147) . Our studies have indicated that immunization of mice with precipitated FT LVS culture filtrate (CF) components can protect Balb/c mice against homologous bacterial challenge.…”
Section: Discussionmentioning
confidence: 99%
“…Until recently, little was known about the extracellular proteins and potential secretion systems of Francisella (133)(134)147). Additionally, there have been no studies on the immunological response to protein antigens found in the media during culture of FT.…”
Section: Precipitation Of Ft Culture Filtrate Components Using Pyrogamentioning
confidence: 99%